The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5489/cuaj.10057
|View full text |Cite
|
Sign up to set email alerts
|

Radical prostatectomy for high-risk clinically localized prostate cancer: a prospective single institution series

Abstract: E156Cite as: Can Urol Assoc J 2011;5(6):E156-E161; http://dx.doi.org/10.5489/cuaj.10057. Epub 2011 Mar 1. AbstractObjective: The objective of this paper is to report on the pathologic and biochemical progression-free outcomes of patients who underwent radical prostatectomy for high-risk localized prostate cancer. Methods: Data was collected prospectively from 299 patients who underwent radical prostatectomy for high-risk clinically localized prostate cancer by 2 surgeons at a single institution. High risk was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In the absence of a well‐conducted randomized trial, there is no definite evidence that one treatment is superior to the other. With modern surgical techniques in experienced hands, there is no increase in morbidity associated with RP in men with high‐risk compared with low‐risk prostate cancer . In our institution, men go home the next day after an open radical prostatectomy with the usual 4 weeks convalescence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a well‐conducted randomized trial, there is no definite evidence that one treatment is superior to the other. With modern surgical techniques in experienced hands, there is no increase in morbidity associated with RP in men with high‐risk compared with low‐risk prostate cancer . In our institution, men go home the next day after an open radical prostatectomy with the usual 4 weeks convalescence.…”
Section: Resultsmentioning
confidence: 99%
“…With modern surgical techniques in experienced hands, there is no increase in morbidity associated with RP in men with high-risk compared with low-risk prostate cancer. [41][42][43]106 In our institution, men go home the next day after an open radical prostatectomy with the usual 4 weeks convalescence. Surgery as monotherapy in high-risk disease (while effective in approximately 40-50% of men) is an antiquated idea and surgery should be considered part of a combined modality approach (where the extra modalities can sometimes be avoided).…”
Section: Resultsmentioning
confidence: 99%
“…[35]; in a series of 375 men with high‐risk disease treated by RP and stage‐dependent adjuvant ADT, the 5‐ and 10‐year CSS was 91.3% and 87.2% respectively. Koupparis et al [36] reported on 299 men with high‐risk disease treated at the Vancouver Prostate Centre, Canada. At a median of 4.7 years follow‐up, 70% of men were free of biochemical relapse and the disease‐specific survival (DSS) was 99%.…”
Section: Outcomes Of Rp For High‐risk Localised Prostate Cancermentioning
confidence: 99%
“…Only RP can discern these patients, in whom monotherapy maybe the only treatment required, thereby avoiding overtreatment with EBRT plus 3 years of ADT. The wide dissection necessary, is capable of achieving specimen‐confined rates of up to 75% [7]. The ePLND can confer a biochemical survival advantage with negative nodes, and with early treatment, outcomes in those with positive nodes and seminal vesicle involvement can also be improved [8].…”
mentioning
confidence: 99%